Tinjauan Hukum Pidana Cheat/Hacking dalam Game Online Berdasarkan Undang-Undang Nomor 11 Tahun 2008 dan Undang-Undang Nomor 19 Tahun 2015 - Pathavi, Williem; Prasetyo, Mujiono Hafidh (Fakultas Syariah INSURI Ponorogo, 2023)
Technological developments in cyberspace today show the development of new ideas and works in various fields. Gaming technology is one of the highlights. Online games are games that connect each player through a network. The increasing number of online game enthusiasts, makes competition between players increase and there is a desire to be superior by taking shortcuts, namely cheating. The more frequent occurrence of cheating/hacking in online game systems raises questions (1) whether Law number 11 of 2008 on Information and Electronic Transactions can be used as a basis for criminal prosecution of perpetrators of cheating/hacking in online game systems? (2) what are the criminal penalty for perpetrators of cheating/hacking in online game systems according to Law number 11 of 2008 concerning Information and Electronic Transactions? The purpose of this normative legal research is to find out the legal provisions governing cheat/hacking in online game systems and criminal penalty that punish the perpetrators in Law number 11 of 2008 on Information and Electronic Transactions, which requires secondary data and library data in reviewing it. The results of his research found that Law number 11 of 2008 on Information and Electronic Transactions can be used as the basis for criminal penalties for perpetrators of cheating/hacking in online game systems because the act of cheating/hacking fulfills the elements of a criminal act contained in Law number 11 of 2008 on Information and Electronic Transactions. Criminal sanctions for perpetrators of cheating/hacking in the online game system are adjusted to the provisions of the article that is violated.